Short-and long-run effects of sustainable forest management practices on West Malaysian log supply : an ARDL Approach. - Abdul Rahim, AS; Mohd Shahwahid, HO (Forest Research Institute Malaysia, 2009)
The Malaysian log supply is facing deficit since 1995; thereafter major timber products have moved from resource surplus to one of deficit. It seems obvious that without planted forest in the future, the timber industries have almost reached the limit for growth. The log supply model for West Malaysia is based on an equation of domestic log supply from natural and planted forests as a function of weighted price of log, annual logging area and royalty of logs. The results showed that the bounds test of log supply model was cointegrated at 10% significance. The short-run analysis revealed that log supply would increase as the price of logs increased. However, in the long run, it would lead to substantial reduction in the log supply. This is because when the price of logs increases, the log supply tends to decrease. It is believed that this is due to controlled production and the stringent harvesting regulation to achieve sustainable forest management. Furthermore, an increase in domestic price of logs would help to compensate for the lost volumes in the long run.